Dual Effects of Human Placenta-Derived Neural Cells on Neuroprotection and the Inhibition of Neuroinflammation in a Rodent Model of Parkinson's Disease. Issue 5 (May 2018) - Kim, Han Wool; Lee, Hyun-Seob; Kang, Jun Mo; Bae, Sang-Hun; Kim, Chul; Lee, Sang-Hun; Schwarz, Johannes; Kim, Gi Jin; Kim, Jin-Su; Cha, Dong Hyun; Kim, Joopyung; Chang, Sung Woon; et al.
Parkinson's disease (PD) is the second most common age-related neurodegenerative disease in the elderly and the patients suffer from uncontrolled movement disorders due to loss of dopaminergic (DA) neurons on substantia nigra pars compacta (SNpc). We previously reported that transplantation of human fetal midbrain-derived neural precursor cells restored the functional deficits of a 6-hydroxy dopamine (6-OHDA)-treated rodent model of PD but its low viability and ethical issues still remain to be solved. Albeit immune privilege and neural differentiation potentials suggest mesenchymal stem cells (MSCs) from various tissues including human placenta MSCs (hpMSCs) for an alternative source, our understanding of their therapeutic mechanisms is still limited. To expand our knowledge on the MSC-mediated PD treatment, we here investigated the therapeutic mechanism of hpMSCs and hpMSC-derived neural phenotype cells (hpNPCs) using a PD rat model. Whereas both hpMSCs and hpNPCs protected DA neurons in the SNpc at comparable levels, the hpNPC transplantation into 6-OHDA treated rats exhibited longer lasting recovery in motor deficits than either the saline or the hpMSC treated rats. The injected hpNPCs induced delta-like ligand (DLL)1 and neurotrophic factors, and influenced environments prone to neuroprotection. Compared with hpMSCs, co-cultured hpNPCs more efficiently protected primary neural precursor cells from midbrain against 6-OHDA as well as induced their differentiation into DA neurons. Further experiments with conditioned media from hpNPCs revealed that the secreted factors from hpNPCs modulated immune responses and neural protection. Taken together, both DLL1-mediated contact signals and paracrine factors play critical roles in hpNPC-mediated improvement. First showing here that hpMSCs and their neural derivative hpNPCs were able to restore the PD-associated deficits via dual mechanisms, neuroprotection and immunosuppression, this study expanded our knowledge of therapeutic mechanisms in PD and other age-related diseases.